Detection process for anti-phishing / Redzuan Nordin - Nordin, Redzuan (2013)
Detection is about the detect the website whereby the website is original or phishing site. Phishing is associated with identity theft over the Internet by luring victims into false assumptions about trust relationships with websites. Data are only given out voluntarily from people in case of existing trust relationships. This project include detection and comparison process using pattern similarity, whereby it will compare the source code of the URL receive with the original source code whereby has been stored in the database. This method is important because it will ensure whether the phishing site or not. If it failed to detect, user will be easily to be a victim of the phishing site. Then if it detected the phishing site, it will pass the URL to the blacklist entry. Then it will inform the result to the user about the phishing site. In order to complete our project, we will use PHP language and mysql database. We also will develop it on the server so that we can avoid the process from being crashed. This is because of the research that we have done many anti-phishing before this implemented in the browser and have the highest probability to crash. Then, we hope our project can help the user from being fraud by the hacker or phisher.